Ghostly Paradoxes : Modern Spiritualism and Russian Culture in the Age of Realism - Vinit︠s︡kiĭ, I. I︠U︡. (Ilʹi︠a︡ I︠U︡rʹevich), 1969- (Book collections on Project MUSE., 2009)
"Foregrounding the important role that nineteenth-century spiritualism played in the period's aesthetic, ideological, and epistemological debates, Ilya Vinitsky challenges literary scholars who have considered spiritualism to be archaic and peripheral to other cultural issues of the time. Ghostly Paradoxes ;s an innovative work of literary scholarship that traces the reactions of Russia's major realist authors to spiritualist events and doctrines and demonstrates that both movements can be understood only when examined together."--Jacket.